Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1039/c3cp50829c
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in porphyrin monolayers: the relation between adsorption configuration and molecular conformation

Abstract: Self-assembled monolayers of meso-5,10,15,20-tetrakis(undecyl)porphyrin copper(II) on a graphite/1-octanoic acid interface have been studied by Scanning Tunnelling Microscopy. Four distinct polymorphs were observed, varying in their unit cell size. Arrays of unit cells of the various polymorphs seamlessly connect to each other via shared unit cell vectors. The monolayers are not commensurate, but coincident with the underlying graphite substrate. The seamless transition between the polymorphs is proposed to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 41 publications
2
39
0
Order By: Relevance
“…Different 2D polymorphs of Cu−C 11 P have been produced by varying the porphyrin concentration in the supernatant solution, with higher-coverage polymorphs forming at higher solution concentrations (51,52). Increasing the porphyrin concentration once a SAM has formed brings about dynamic changes to the SAM only around defects, however, indicating that the SAMs are kinetically trapped, and this trapping takes only seconds to manifest after first application of the solution to the substrate.…”
mentioning
confidence: 99%
“…Different 2D polymorphs of Cu−C 11 P have been produced by varying the porphyrin concentration in the supernatant solution, with higher-coverage polymorphs forming at higher solution concentrations (51,52). Increasing the porphyrin concentration once a SAM has formed brings about dynamic changes to the SAM only around defects, however, indicating that the SAMs are kinetically trapped, and this trapping takes only seconds to manifest after first application of the solution to the substrate.…”
mentioning
confidence: 99%
“…These domain boundaries provide a lot of structural information and their analysis greatly aids the determination of atomic structures representing STM images. Initially, [115] the central L phase of the Cu-C 11 P polymorph shown in Fig. 4 was attributed to a different polymorph then label "B" as its lattice parameters differed appreciably from those of the large domains of L. However, PBE-D3 and QM/MM calculations revealed that the potential-energy surface is very flat in the direction that causes this shift.…”
Section: Rationalizing Interface Structuresmentioning
confidence: 98%
“…[87,88,113,115,116,117,118,119] Relaxing this constraint allows much better fits to be made to the vector lengths, resulting in an overall lower energy penalty for commensurate-lattice production. Table 1 gives the QM/MM optimized lattice parameters defined in Fig.…”
Section: Incommensurate Sam and Substrate Latticesmentioning
confidence: 99%
See 2 more Smart Citations